Pengaruh Tingkat Tuntutan Pemrosesan Informasi Selama Pembelajaran terhadap Kemampuan Mengingat Kembali Materi Akuntansi pada Siswa Kelas X SMK - Miftah Indiraihan Derby; Silmi Alya Sopianti; Nurzika Alya Ramadanti; Appriana Mutipena Saragih; Nurul Aulia Yolanda; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study examined the effect of information processing demands during instruction on students’ ability to retrieve general journal material in tenth-grade vocational high school students. A pretest-posttest experimental design with a control group was employed. Twenty-nine students participated at the initial stage, but complete data were obtained from only 19 students, consisting of nine students in the experimental group and ten students in the control group. The experimental group received denser and faster material presentation with limited processing pauses, whereas the control group received the same material gradually and in a more structured manner. Retrieval ability was assessed using an objective test administered six days after the intervention. The data were analyzed using analysis of covariance, with pretest scores entered as a covariate. The findings showed that prior ability significantly contributed to posttest performance, whereas the effect of the learning condition was not significant. The manipulation check also revealed no meaningful difference in perceived information processing demands between the two groups. These findings suggest that differences in presentation speed and density during a brief single-session intervention were insufficient to produce distinct cognitive experiences and retrieval outcomes. The results should be interpreted in light of the small sample size, participant attrition, possible ceiling effects, short intervention duration, and limited sensitivity of the retrieval measure.